A Naive Glance to Postmodern Architecture in 21st Century: Termination or Transformation? - Lerzan ARAS (Uludağ University Journal of The Faculty of Engineering, 2015)
Too many years have past since Venturi’s Las Vegas analysis. Our taste, point of views, and of course our societal structure has changed. Gene Roddenberry’s cult TV series Star Trek which remained years on screen, turned out to be naive, and charming but also deficient for us. Communication channels have been increased. Technology’s rapid progress has surprised even itself. Lyotard’s analysis about postmodern conditions, or Hassan’s renewed descriptions about postmodernism should be moved to another dimension. As Hassan speaks, "... Postmodernism became more than an artistic style or historical trend or Zeitgeist, it is a way of reading all our signs under the mandate of misprision." (Hassan, 2003) For some critics, the postmodern architecture is about to come to a ‘cul de sac’ while we are experiencing the first quarter of the 21st century. But the matter for question is, whether the postmodern architecture is undergoing a transformation, or the point at issue is a termination. This study aims to evaluate postmodern architecture at this threshold after a short reminder of the past.